Breaking Down Status - Kaiponanea T. Matsumura (Washington University Law Review, 2021)
The law regulates some of society’s most significant relationships through status. Yet social and legal changes can diminish a status’s effectiveness and importance. The debates surrounding worker classification and nonmarital relationship recognition provide two pressing examples. By some estimates, over one quarter of all U.S. workers are part of the gig economy. If these gig workers are classified as employees, many rights will flow to them by virtue of that status; if they are instead classified as independent contractors, they get almost none of them. This binary approach exists in the family law context as well. Over 35 million adults are in committed nonmarital relationships marked by some combination of physical or emotional intimacy, property sharing, cohabitation, and shared childrearing. But the law will treat the overwhelming majority of them as single, meaning that unlike spouses, they will find themselves without legal protections and subsidies throughout the relationship and at its end. The problem in both contexts is a mismatch between established statuses and emerging social realities. This Article investigates the persistence of status-based regulation through the lenses of employment and marriage. In doing so, it makes four contributions. First, it identifies the relevant features of status and the tradeoffs inherent in regulating through status. Second, using the examples of gig workers and nonmarital partners, it shows how the features of status lead to the emergence of regulatory voids. Third, it argues that status-based regulation is inevitable, both because of practical political considerations and because the most obvious alternative to status-based regulation, contract, is necessarily shaped by the relational context and therefore devolves to status. Fourth, with reform as the only possibility, the Article proposes institutional design questions to guide future reform efforts.
Keywords: Worker classification; Nonmarriage; Status-based regulation; Employment law; Family law; Gig economy